Characterization of self-adhesive structural tapes modified with polyvinyl acetal resins. (June 2016) - Kowalczyk, Agnieszka; Kowalczyk, Krzysztof
Abstract: Thermally curable self-adhesive structural tapes (SATs) based on epoxy resin/acrylate copolymer composition and modified with three types of polyvinyl acetal resins (i.e. polyvinyl butyral- stat -acetal and polyvinyl butyrals) were prepared. The influence of polyvinyl resins addition on reactivity and self-adhesive features of SATs as well as on mechanical resistance of aluminum-SAT-aluminum joints was investigated. It was revealed that polyacetal resin addition (0.5 wt. part/100 wt. parts of adhesive composition) increases the adhesion of SATs to a steel substrate and, moreover, improves the overlap shear strength of thermally cured joints. The type and content of applied polyvinyl acetals influence the enthalpy of the photocrosslinking process, crosslinking degree as well as the epoxy groups conversion of SATs matrix.